1994
DOI: 10.1007/bf00370718
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of severe atopic dermatitis with extracorporeal photopheresis

Abstract: Extracorporeal photopheresis using UVA irradiation of enriched lymphocytes in the presence of 8-methoxypsoralen (8-MOP) as a photoactivatable substrate has been employed for the treatment of several immunologically mediated disorders. We report on the first three patients subjected to extracorporeal photopheresis for severe atopic dermatitis. All patients had a lifelong history of atopic skin inflammation, and their disease had finally become resistant to well-established therapeutic regimes. Extracorporeal ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
8

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(53 citation statements)
references
References 16 publications
1
44
0
8
Order By: Relevance
“…Extracorporeal photopheresis may be a successful therapy for some patients, but due to the high costs and possible side-effects of long-term treatment, this therapy should be limited to severe cases (96).…”
Section: Current Therapeutic Options In Admentioning
confidence: 99%
“…Extracorporeal photopheresis may be a successful therapy for some patients, but due to the high costs and possible side-effects of long-term treatment, this therapy should be limited to severe cases (96).…”
Section: Current Therapeutic Options In Admentioning
confidence: 99%
“…Recently, four open clinical trials have suggested that long-term photopheresis therapy may be safe and effective in severe cases of AD [7,8,9,10]. Photopheresis has also been found to improve laboratory correlates of active AD including hyperimmunoglobulinemia E, and elevated levels of ECP, sIL-2R and soluble E-selectin [10].…”
Section: Introductionmentioning
confidence: 99%
“…Phototherapeutische Verfahren sind ein wichtiger Bestandteil im Behandlungskonzept der AD. Dabei werden unterschiedliche Therapiemodalitäten wie UVA, UVB [9,10], PUVA [12], UVA-1 [11] und für sehr schwere Fälle die extrakorporale Photophorese [14] eingesetzt (Übersicht in [6]). Nach den guten Erfahrungen einer Kombination von Meerwasserbädern und Sonnenbestrahlung am Toten Meer bei Patienten mit Psoriasis [7] wurde diese Behandlungsform auch bei Patienten mit AD angewendet [5].…”
Section: Methodik Patientenunclassified